2020
DOI: 10.18231/j.ijcbr.2020.012
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity C-reactive protein, Malondialdehyde and their association with Glycated hemoglobin (HbA1c)in type 2 diabetes patients

Abstract: Type 2 diabetes mellitus is a major public health problem worldwide and accompanied by enduring vascular complications, which leads to morbidity and mortality. Inflammation play major role in the pathogenesis of type 2 diabetes mellitus. High sensitivity C-reactive protein is an acute phase protein synthesized by the liver and has been revealed as sensitive, systemic inflammatory marker . Oxidative stress, low grade systemic inflammation contributes to insulin resistance and is linked to the characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
1
0
1
Order By: Relevance
“…In a study of Iraqi Arab females with type 2 diabetes mellitus (n = 51) and control subjects (n = 31), serum MDA was significantly elevated in diabetic patients at 6.78 ± 1.21 nmol/ml compared to controls at 3.82 ± 0.77 nmol/ml (p < 0.001) [15]. Among Indian participants, MDA levels were significantly higher in type 2 diabetic patients (n = 100) compared to non-diabetic individuals (n = 100), with measurements of 5.9 ± 1.6 μmol/L and 1.8 ± 0.6 μmol/L, respectively (P = 0.029) [16]. Another study involving 139 Nigerian men and women found that serum malondialdehyde levels were elevated in type 2 diabetes patients, measuring 2.1 ± 0.1 μmol/L, compared to control subjects at 0.7 ± 0.0 μmol/L (P = 0.01) [17].…”
Section: Discussionmentioning
confidence: 89%
“…In a study of Iraqi Arab females with type 2 diabetes mellitus (n = 51) and control subjects (n = 31), serum MDA was significantly elevated in diabetic patients at 6.78 ± 1.21 nmol/ml compared to controls at 3.82 ± 0.77 nmol/ml (p < 0.001) [15]. Among Indian participants, MDA levels were significantly higher in type 2 diabetic patients (n = 100) compared to non-diabetic individuals (n = 100), with measurements of 5.9 ± 1.6 μmol/L and 1.8 ± 0.6 μmol/L, respectively (P = 0.029) [16]. Another study involving 139 Nigerian men and women found that serum malondialdehyde levels were elevated in type 2 diabetes patients, measuring 2.1 ± 0.1 μmol/L, compared to control subjects at 0.7 ± 0.0 μmol/L (P = 0.01) [17].…”
Section: Discussionmentioning
confidence: 89%
“…Các nghiên cứu trên thế giới cũng cho thấy tỷ lệ mắc ĐTĐ typ 2 tăng theo tuổi và thường gặp ở phụ nữ. Nếu lứa tuổi 30-40 tuổi có tỷ lệ mắc ĐTĐ typ 2 là 40% thì ở lứa tuổi 40-50 tuổi tỷ lệ này là 60% (7) . Nghiên cứu tại Ai Cập (2018) nhận thấy ĐTĐ typ 2 gặp nhiều nhất ở phụ nữ (82,9%) với tuổi trung bình là 50.83±8.26 tuổi (4) .…”
Section: đặC đIểmunclassified